2022
DOI: 10.1097/iae.0000000000003463
|View full text |Cite
|
Sign up to set email alerts
|

A Common Finding in Foveal-Sparing Extensive Macular Atrophy With Pseudodrusen Implicates Basal Laminar Deposits

Abstract: Purpose: To characterize structural and clinical alterations preceding the diffuse macular atrophy in extensive macular atrophy with pseudodrusen (EMAP) and their evolution toward atrophic changes.Methods: A retrospective chart review was performed of patients with early-onset reticular pseudodrusen (i.e., pre-EMAP) younger than 55 years and EMAP with foveal sparing. Patients were included if they had complete medical records and multimodal imaging.Results: A total of 12 patients were reviewed, of whom 4 of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Indeed, knowledge regarding the early retinal and functional alterations occurring in the initial stage of EMAP is currently limited in the literature and deserves further in-depth studies. 48 In conclusion, our study prospectively investigated the structural and spatial progression of RPE atrophy in EMAP patients. Based on our extensive analyses, we propose the first disease classification.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, knowledge regarding the early retinal and functional alterations occurring in the initial stage of EMAP is currently limited in the literature and deserves further in-depth studies. 48 In conclusion, our study prospectively investigated the structural and spatial progression of RPE atrophy in EMAP patients. Based on our extensive analyses, we propose the first disease classification.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, knowledge regarding the early retinal and functional alterations occurring in the initial stage of EMAP is currently limited in the literature and deserves further in-depth studies. 48…”
Section: Discussionmentioning
confidence: 99%
“…As recently demonstrated, this finding may result from a non-neovascular splitting of the RPE/Bruch membrane complex representing thick basal laminar deposits on OCT B-scans. 27,28 Despite a higher specificity compared with the DLS, the diagnostic performance of SLGs as a biomarker for NE-MNV appears inferior to the DLS, as confirmed by Youden's index. Moreover, SLGs and DLS cannot be considered interchangeably, as they are more likely complementary predictors in NE-MNV.…”
Section: Discussionmentioning
confidence: 97%
“…Reticular pseudodrusen (RPD), also referred to as subretinal drusenoid deposits (SDDs), are differentiated from conventional drusen in that they are located above the RPE [23 ▪▪ ,25]. They are often difficult to visualize on clinical examination but can be more apparent with the use of fundus autofluorescence (FAF), near-infrared reflectance (NIR), and OCT [26 ▪ ].…”
Section: Early Detection Of Geographic Atrophymentioning
confidence: 99%
“…A rare and aggressive variant of atrophic AMD referred to as extensive macular atrophy with pseudodrusen (EMAP) has been described as early-onset (<60 years), bilateral, and severe macular atrophy associated with numerous deposits resembling reticular pseudodrusen which extend towards the midperiphery and are accompanied by peripheral pavingstone degeneration [25,29]. The differentiating factor between EMAP as compared to the reticular pseudodrusen found in AMD is that patients with EMAP do not exhibit the same cardiovascular risk factors which are found in AMD patients [25]. It is suggested that RPD/SDDs should be included in updated AMD classification systems, risk calculators, and clinical trials.…”
Section: Early Detection Of Geographic Atrophymentioning
confidence: 99%